A scoping review on occupational therapy services with forcibly displaced individuals in low to middle income countries - Humairaa Hassan; Juwairiyya Paruk; Heema Gordhan; Lebogang Maseko (Discover Social Science and Health, 2024)
Abstract This study underscores the distinctive role of occupational therapy in advancing the health and wellbeing of forcibly displaced individuals (FDIs), who often encounter contextual and systemic barriers and medical complications that prevent them from engaging in daily tasks. These injustices can be mitigated through health promotion and prevention strategies that aim to enhance participation in daily life activities. There has been limited research in low- to middle-income countries (LMICs) in relation to occupational therapy services for FDIs despite most FDIs originating from LMICs. To address this gap, this study adopted Arksey and O’Malley’s framework for a scoping review to consolidate existing knowledge on the occupational therapy health promotion and prevention of disease and disability services for FDIs in LMICs. Searches were conducted on six online databases. Six studies aligned with the inclusion criteria. Findings revealed that most occupational therapy services are directed towards refugees in Jordan, which contains one of the largest refugee camps. FDIs from Africa and internally displaced people receive the least number of interventions. The occupational therapy services outlined in the six sources primarily consist of health education talks, early childhood interventions, and health promotion activities centred around various occupations such as work and sports groups. Recommendations for policy guidelines include incorporating occupational therapy services within the stipulated FDI services. Our approach aims to situate the contribution of occupational therapy health promotion and prevention of disease and disability services within the broader context of FDIs’ overall health and wellbeing.